The leadership dimensions of the Sisters of Jesus Good Shepherd "Pastorelle" in the Educational Pastoral Ministry - Pamplona, Ales Paz O. (Animo Repository, 2010)
This study seeks to describe and analyze how the Sisters of Jesus Good Shepherd Pastorelle reinterpret and live out the charism of pastoral care as school leaders and managers. The focus is on their leadership dimensions in the educational pastoral ministry based on the theoretical propositions derived from the life and teachings of their Founder, Blessed James Alberione, and the impact of their leadership practices on the school communities they serve. In this study, the findings came in the form of an emerged framework of leadership in the educational pastoral ministry which is a concrete expression of the charism of the Pastorelle Sisters.